The Degree Of Use And The Variety Of Prewriting Activities Employed In UHB 1412 Class In UTM - Shamsudin , Sarimah; Raja Abd Rahman, Raja Intan Dewiasyikin (2010)
This research aims to investigate the types of prewriting activities conducted in UHB 1412 class and to what extent it has been used. The effectiveness of the prewriting activities that have been used is also being identified. Besides that, it also investigates the students’ and teachers’ perceptions on the importance of the prewriting activities in the writing class. A total of 100 students in Universiti Teknologi Malaysia (UTM) who are taking the UHB 1412 class and four Universiti Teknologi Malaysia (UTM) lecturers who are teaching UHB 1412 class participated in this study. The research instruments used for this study were questionnaires and interview. 100 sets of questionnaires were distributed to get feedback from the students on the use of prewriting activities when they are learning writing in the UHB 1412 class. Interview sessions were conducted with four lecturers to identify the types of prewriting activities that they used in their UHB 1412 class and to what extent these activities have been used in their teaching of writing in the UHB 1412 class. It is to ensure that there is no contradiction in the data collected. Thus, giving this study greater validity. Results from the findings indicate the following: 1) All the lecturers do conduct prewriting activities when teaching writing in their UHB 1412 class. 2) The most frequent prewriting activities conducted in the classroom are brainstorming and discussion. 3) Students are aware that prewriting activities could improve their writing. 4) Lecturers find it helpful for students to improve their writing. Finally, the pedagogical implications of the findings and recommendations for the future research are being suggested.